Central projections of antennular chemosensory and mechanosensory afferents in the brain of the terrestrial hermit crab (Coenobita clypeatus; Coenobitidae, Anomura) - Tuchina, Oksana; Koczan, Stefan; Harzsch, Steffen; Rybak, Jürgen; Wolff, Gabriella; Strausfeld, Nicholas J.; Hansson, Bill S. (Frontiers in Neuroanatomy, 2015)
The Coenobitidae (Decapoda, Anomura, Paguroidea) is a taxon of hermit crabs that includes two genera with a fully terrestrial life style as adults. Previous studies have shown that Coenobitidae have evolved a sense of spatial odor localization that is behaviorally highly relevant. Here, we examined the central olfactory pathway of these animals by analyzing central projections of the antennular nerve of Coenobita clypeatus, combining backfilling of the nerve with dextran-coupled dye, Golgi impregnations and three-dimensional reconstruction of the primary olfactory center, the antennular lobe. The principal pattern of putative olfactory sensory afferents in C. clypeatus is in many aspects similar to what have been established for aquatic decapod crustaceans, such as the spiny lobster Panulirus argus. However, there are also obvious differences that may, or may not represent adaptations related to a terrestrial lifestyle. In C. clypeatus, the antennular lobe dominates the deutocerebrum, having more than one thousand allantoid-shaped subunits. We observed two distinct patterns of sensory neuron innervation: putative olfactory afferents from the aesthetascs either supply the cap/subcap region of the subunits or they extend through its full depth. Our data also demonstrate that any one sensory axon can supply input to several subunits. Putative chemosensory (non-aesthetasc) and mechanosensory axons represent a different pathway and innervate the lateral and median antennular neuropils. Hence, we suggest that the chemosensory input in C. clypeatus might be represented via a dual pathway: aesthetascs target the antennular lobe, and bimodal sensilla target the lateral antennular neuropil and median antennular neuropil. The present data is compared to related findings in other decapod crustaceans.